Respuesta :

Answer:

without division its a little hard but 2 is divisible by any number so...

Step-by-step explanation:

Answer:

Proven below in the explanation

Step-by-step explanation:

Given that:

2x⁴-6x³+3x²+3x-2  ............. (1)

x²-3x+2 ................................ (2)

To proof that equation (1) is exactly divisible by equation (2), substitute an integer for 'x' in the two equations so as to form a whole number.

Assume x = 1

∴For equation (1)

  = 2(1)⁴-6(1)³+3(1)²+3(1)-2

  = 2 - 6 + 3 + 3 - 2

  = 0

∴For equation (2)

  = (1)²-3(1)+2

  = 1 - 3 + 2

  = 0

For x = 1, both equations are zero'0'

0/0 = 0